Should I stay or should I go? Challenges and Opportunities in Music-based Public Engagement - Giovanardi, Massimo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
This paper critically reflects on the researcher’s effort to stimulate public engagement around the themes of inclusivity and sustainable tourism through arts-based approaches. This effort resulted in a music show on mobilities, tourism and cultural diversities performed at the IT.A.CÀ festival in Bologna[1]. Here, a songwriting-based celebration of values such as openness and inclusivity was coupled with an attempt to share with a wider audience what are the main challenges of researchers working on sustainable tourism development, thus promoting dialogue and exchange of ideas. Presenting the main obstacles and opportunities encountered, the paper performs a critical evaluation of the intervention with the aim to improve future music-based contribution to the festival I.TA.CÀ and other public engagement occasions. [1] A sample of the show can be viewed at https://www.youtube.com/watch?v=mNnwzONhsPE